Upplevelserummet : Hur rummet påverkar elevers motivation till kreativt skapande - Tönnesen, Jenny (2015)
"The experienceroom- How the room affects students' motivation to creativity" is my thesis at the Department of Music and Media at Luleå University of Technology.In the background the reader is given an orientation in the concept of the experienceroom and various motivation and creativity theories. There, also presents Waldorf education, Goethe's color theory and the anthroposophic architecture, all in order to allow the reader to understand the full context of the essay.The aim of the thesis was to create knowledge about the experienceroom's significance for schoolchildren in grades eight based on the concepts of creativity and motivation.I have conducted my research on the basis of a qualitative research with literature and semi-structured interviews as research tools. I have in the study interviewed eight students aged 14-15 years in a Waldorf school in Stockholm.The result of the interviews is divided into three main headings themed experienceroom, creativity and motivation. Data from the interviews suggest that the experienceroom has its own value independent of the interaction between other students and teachers. Crucial interior factors that affect students' creativity and motivation are the experienceroom's natural light, color, form, architecture, materials and view.The essay terminates with a set of conclusions which, among other things, affect the internal and external motivation in students, how creative frames affect students' creativity and how the experienceroom design affects students physically and spiritually. Validerat; 20150605 (global_studentproject_submitter)